2019
DOI: 10.1371/journal.pone.0214125
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Schistosoma mansoni-derived DNA in human urine samples by loop-mediated isothermal amplification (LAMP)

Abstract: BackgroundSchistosoma mansoni is the main species causing hepatic and intestinal schistosomiasis in Sub-Saharan Africa, and it is the only species in South America. Adult stages of the parasite reside in the mesenteric venous plexus of infected hosts, and eggs are shed in feces. Collecting patient stool samples for S. mansoni diagnostic purposes is difficult in large-scale field trials. Urine samples would be an alternative approach for molecular S. mansoni detection since they have several advantages over sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The serum-based real-time PCR performed excellently with 96.3% sensitivity, whereas the urine-based real-time PCR showed the lowest sensitivity (33.3%) and the lowest Kappa agreement with the "gold standard" (0.119). Various other studies indicate that the diagnosis of S. mansoni infection is possible using urine as a source of DNA [32][33][34][35]. In our study, the performance of the urine-based real-time PCR was even lower than the KK method, despite the fact that the DNA in the urine was stabilized with a special reagent.…”
Section: Discussionmentioning
confidence: 53%
“…The serum-based real-time PCR performed excellently with 96.3% sensitivity, whereas the urine-based real-time PCR showed the lowest sensitivity (33.3%) and the lowest Kappa agreement with the "gold standard" (0.119). Various other studies indicate that the diagnosis of S. mansoni infection is possible using urine as a source of DNA [32][33][34][35]. In our study, the performance of the urine-based real-time PCR was even lower than the KK method, despite the fact that the DNA in the urine was stabilized with a special reagent.…”
Section: Discussionmentioning
confidence: 53%
“…As complicated body fluid, urine and genital secretion had been applied to detecting T. vaginalis on the basis of nucleic acid, and the sensitivity of which were 64-100% for urine samples and 81-100% to genital secretion swabs [45,46]. Previous studies have shown that LAMP reactions were not inhibited in spiked urine specimens [47]. Nevertheless, due to the usage of the wild type enzyme in the LAMP approach, unwanted activity of DNA polymerase in the process of setup possibly led to fail in reproducible amplification.…”
Section: Discussionmentioning
confidence: 99%
“…As complicated body fluid, urine and genital secretion had been applied to detecting T. vaginalis on the basis of nucleic acid, and the sensitivity of which were 64% -100% for urine samples and 81% -100% to genital secretion swabs [45,46]. Previous studies have shown that LAMP reactions were not inhibited in spiked urine specimens [47]. Nevertheless, due to the usage of the wild type enzyme in the LAMP approach, unwanted activity of DNA polymerase in the process of setup possibly led to fail in reproducible amplification.…”
Section: Discussionmentioning
confidence: 99%